Feasibility and preliminary efficacy of the 'HEYMAN' healthy lifestyle program for young men: a pilot randomised controlled trial. Issue 1 (December 2017) - Ashton, Lee; Morgan, Philip; Hutchesson, Melinda; Rollo, Megan; Collins, Clare
Abstract Background In young men, unhealthy lifestyle behaviours can be detrimental to their physical and/or mental health and set them on a negative health trajectory into adulthood. Despite this, there is a lack of evidence to guide development of effective health behaviour change interventions for young men. This study assessed the feasibility and preliminary efficacy of the 'HEYMAN' (Harnessing Ehealth to enhance Young men's Mental health, Activity and Nutrition) healthy lifestyle program for young men. Methods A pilot RCT with 50 young men aged 18–25 years randomised to the HEYMAN intervention (n  = 26) or waitlist control (n  = 24). HEYMAN was a 3-month intervention, targeted for young men to improve eating habits, activity levels and well-being. Intervention development was informed by a participatory research model (PRECEDE-PROCEED). Intervention components included eHealth support (website, wearable device, Facebook support group), face-to-face sessions (group and individual), a personalised food and nutrient report, home-based resistance training equipment and a portion control tool. Outcomes included: feasibility of research procedures (recruitment, randomisation, data collection and retention) and of intervention components. Generalized linear mixed models estimated the treatment effect at 3-months for the primary outcomes: pedometer steps/day, diet quality, well-being and several secondary outcomes. Results A 7-week recruitment period was required to enrol 50 young men. A retention rate of 94% was achieved at 3-months post-intervention. Retained intervention participants (n  = 24) demonstrated reasonable usage levels for most program components and also reported reasonable levels of program component acceptability for attractiveness, comprehension, usability, support, satisfaction and ability to persuade, with scores ranging from 3.0 to 4.6 (maximum 5). No significant intervention effects were observed for the primary outcomes of steps/day (1012.7, 95% CI = −506.2, 2531.6, p  = 0.191, d  = 0.36), diet quality score (3.6, 95% CI = −0.4, 7.6, p  = 0.081, d  = 0.48) or total well-being score (0.4, 95% CI = −1.6, 2.5, p  = 0.683, d  = 0.11). Significant intervention effects were found for daily vegetable servings, energy-dense, nutrient-poor foods, MVPA, weight, BMI, fat mass, waist circumference and cholesterol (allp  < 0.05). Conclusions The HEYMAN program demonstrated feasibility in assisting young men to make some positive lifestyle changes. This provides support for the conduct of a larger, fully-powered RCT, but with minor amendments to research procedures and intervention components required. Trial registration Australian New Zealand Clinical Trials RegistryACTRN12616000350426 .